2014
DOI: 10.1002/maco.201407638
|View full text |Cite
|
Sign up to set email alerts
|

Anodic dissolution of cobalt in aqueous sodium nitrate solution at high current densities

Abstract: The present work focuses on the anodic dissolution of cobalt and the surface texture development in 2.9 mol/L sodium nitrate solution under current controlled conditions at 25 and 30 A/cm2. Before the electrochemical experiments the crystallographic orientation of the samples was investigated by EBSD. The anodic behavior of cobalt as well as the surface topography was microscopically observed using a special electrochemical through flow cell in-operando during the current controlled dissolution. The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…[ 4 ] A major example is the tooling of very hard and complex‐shaped turbine blades made of nickel superalloys. ECM is based on anodic dissolution, which makes it suitable to study the dissolution of various materials at high current densities; see, for example, Schneider et al, [ 5–7 ] and references therein. Beyond that, ECM is used in a variety of applications, such as for surface polishing, [ 8–11 ] stainless steel machining microelements with ultrashort voltage pulses, [ 12,13 ] or for the machining of three‐dimensional (3D) microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] A major example is the tooling of very hard and complex‐shaped turbine blades made of nickel superalloys. ECM is based on anodic dissolution, which makes it suitable to study the dissolution of various materials at high current densities; see, for example, Schneider et al, [ 5–7 ] and references therein. Beyond that, ECM is used in a variety of applications, such as for surface polishing, [ 8–11 ] stainless steel machining microelements with ultrashort voltage pulses, [ 12,13 ] or for the machining of three‐dimensional (3D) microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…21 Schneider et al performed research of the anodic dissolution behavior and surface texture development of cobalt at high current densities. 22 Ge et al investigated the electrochemical dissolution behavior of nickel-based cast superalloy K423A in NaNO 3 solution and established a qualitative dissolution model. 23 Weber et al investigated the electrochemical dissolution of three types of cast iron in NaNO 3 and found that the material microstructure and the electrolyte pH have an impact on the dissolution potential.…”
mentioning
confidence: 99%